2011
DOI: 10.1016/j.expneurol.2011.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Breathing patterns after mid-cervical spinal contusion in rats

Abstract: Respiratory failure is the leading cause of death after cervical spinal injury. We hypothesized that incomplete cervical spinal injuries would alter respiratory pattern and initiate plasticity in the neural control of breathing. Further, we hypothesized that the severity of cervical spinal contusion would correlate with changes in breathing pattern. Fourteen days after C4–C5 contusions, respiratory frequency and tidal volume were measured in unanesthetized Sprague Dawley rats in a whole body plethysmograph. Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 43 publications
(57 reference statements)
9
61
0
Order By: Relevance
“…Simon et al (1995) showed that individuals with high cervical SCI initiated inspiratory electromyogram (EMG) activity at a lower end-tidal CO 2 as compared to able-bodied controls (i.e., after SCI there was a lower CO 2 recruitment threshold). A similar finding has been reported in a rat model (Golder et al, 2011). A reduction in the CO 2 “apneic threshold” after SCI could reflect an increase in the CO 2 sensitivity of respiratory neurons and/or networks.…”
Section: Osa and Scisupporting
confidence: 91%
“…Simon et al (1995) showed that individuals with high cervical SCI initiated inspiratory electromyogram (EMG) activity at a lower end-tidal CO 2 as compared to able-bodied controls (i.e., after SCI there was a lower CO 2 recruitment threshold). A similar finding has been reported in a rat model (Golder et al, 2011). A reduction in the CO 2 “apneic threshold” after SCI could reflect an increase in the CO 2 sensitivity of respiratory neurons and/or networks.…”
Section: Osa and Scisupporting
confidence: 91%
“…Several contusion models at mid-cervical levels (C3, C4, C5) that show chronic abnormalities in respiratory parameters have been developed in the rat. [22][23][24][25] The extension of a contusion injury model to the mouse provides opportunities for manipulating genes of interest and for evaluating their role in relevant outcome measures affected by cervical spinal contusion such as forelimb motor function, respiratory function, and neuropathic pain.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this model allows for the use of genetically modified animals for exploring the function of specific genes in the pathophysiology of respiratory motor neuron degeneration and functional respiratory compromise following cervical SCI. [19][20][21][22][23] Methods…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory deficits following cervical SCI have been studied using various animal models that impair ventilation without the need for chronic mechanical ventilatory support, including midline (el-Bohy et al, 1998; Golder et al, 2011; Lane et al, 2012) vs. unilateral contusion (Alvarez-Argote et al, 2015; Baussart et al, 2006; Nicaise et al, 2013; Nicaise et al, 2012a; Nicaise et al, 2012b), or transection (Imagita et al, 2015). A well-established model of SCI, spinal hemisection of the C2 segment of the cervical spinal cord (SH) abolishes descending neural drive to ipsilateral phrenic motoneurons, transiently interrupting ipsilateral phrenic motoneuron activity and inducing DIAm paralysis (Fuller et al, 2006; Goshgarian, 2003; Gransee et al, 2013, 2015; Mantilla et al, 2013a; Mantilla et al, 2013b; Porter, 1895).…”
Section: Recovery Of Rhythmic Diaphragm Activity After Cervical Spmentioning
confidence: 99%